Non-Alcoholic Fatty Liver Disease and the Risk of Liver Fibrosis in Chronic Hepatitis B Patients - Andri Sanityoso Sulaiman; Irsan Hasan; Cosmas Rinaldi A. Lesmana; Juferdy Kurniawan; Chyntia Olivia M. Jasirwan; Saut Horas H. Nababan; Kemal Fariz Kalista; Gita Aprilicia; Rino Alvani Gani (Jurnal Penyakit Dalam Indonesia)
Introduction. Prevalence of non-alcoholic fatty liver disease (NAFLD) is increasing throughout the world due to sedentary lifestyle and dietary habit, including in patients with chronic hepatitis B (CHB). In several studies, advanced of liver disease were more likely observed among those CHB patients with NAFLD. NAFLD might increase the risk of liver disease progression in CHB patients, but prior investigations were still limited. This study aimed to determine the association between NAFLD and risk of liver fibrosis in CHB patients. Methods. All patients with positive serum hepatitis B surface antigen in the Hepatobilier Data Registry, Cipto Mangunkusumo Hospital, were included in this study. Based on abdominal ultrasonography, patients were divided into two group (group I: non-NAFLD – hepatitis B patients vs. group II: NAFLD – hepatitis B patients). Data demographic and clinical examination were collected. Significant liver fibrosis was defined as stage liver fibrosis above 7 kPa (≥ F2). Logistic regression was used to identify NAFLD as risk factor for significant fibrosis. Variables were expressed as prevalence odd ratio (POR) with 95% CI. P values <0.05 were considered statistically significant. Results. Among 130 hepatitis B patients, 45 patients (34.6%) were diagnosed with NAFLD. Of 45 patients in group II, 36 patients (80%) had significant liver fibrosis. It was observed that a higher percentage of patients in group II were HBeAg negative compared to those in group I (66.7% vs. 35.9%; p=0.038). Furthermore, group II also displayed higher levels of liver stiffness compared to group I (12.22 (8.6 kPa) vs. 8.57 (7.8 kPa); p 0.016). In multivariate analysis, NAFLD was significantly associated with significant liver fibrosis (POR: 5.87; CI95%: 2.48 – 13.86; p < 0.001) after adjusted with HBeAg status. Conclusion. NAFLD associated with the higher risk of liver fibrosis in patients with hepatitis B. Modification of lifestyle and potential therapeutic intervention may help in reducing the progression of liver fibrosis.